Influence of abiotic factors on the effectiveness of Bacillus thuringiensis israelensis (Berliner, 1911) against larvae of Aedes aegypti (Linnaeus, 1762) - Santos da Silva, Antonia (Revista Cubana de Medicina Tropical, 2020)
Methods: we conducted bioassay experiments in the campus of the CESC / UEMA. With use of 20 Twenty cement tanks, of these, were used, 10 of which were exposed to environmental factors, and only. Of these, 5 were treated and 5 served as controls. The other 10 tanks were placed in the shade, also again 5 were treated and 5 untreated were not (control). After treatment, the 25 stage L 3 larvae were placed in 25 L 3 each stage tank and mortality. Mortality readings were taken after 24 hours and every 7 days. Weekly water samples were collected from all tanks to measure once a week to check the number of viable spores and evaluate bacterial recycling.Results and discussion: the larvicidal efficacy: The larvicide showed initial efficacy, killing 100 % of the larvae in tanks that were located both in the sun and in the shade. Environmental factors, sunlight, temperature and rainfall negatively affected the effectiveness of the product, because for there was a reduction in the effectiveness of the product throughout the experiment. It was observed variation in the number of spores during the development of the experiment demonstrating, showing that the bacterium has potential recyclability.Conclusion: these data serve as parameters for improving to in Bti-based insecticides, in order to make the with a view to making formulations more suited toin keeping with the environmental conditions of our region.Objective: to evaluate the influence of abiotic factors on the effectiveness of B. thuringiensis var. israelensis to against larvae of Ae. aegypti.Introduction: Bacillus thuringiensis, has been used worldwide for the control of mosquitoes, particularly in combating Aedes aegypti. Various formulations have been made however, the effectiveness of these insecticides vary varies considerably according to the environmental conditions. © 2014, Editorial Ciencias Medicas. All rights reserved.